Mechanisms of the Bushen Huoxue formula in the treatment of osteoarthritis based on network pharmacology-molecular targets. Issue 32 (12th August 2022) - Pang, Tingting; Liu, Chang; Yao, Junjie; Li, Jiahui; Li, Zhongxu; Lou, Huijuan; Lei, Siyuan; Zhang, Jiangchun; Dong, Li; Wang, Yufeng
Abstract : Background: Osteoarthritis is a common degenerative disease with a high incidence, high disability rate, and poor prognosis. Clinical studies have shown that Bushen Huoxue formula can relieve joint swelling and pain and improve limb function and joint mobility, but there is a lack of high-quality scientific basis. Using network pharmacology and molecular docking technology to study the mechanism of Bushen Huoxue formula in the treatment of osteoarthritis. Methods: First, the active ingredients and corresponding target predictions of the formula were obtained through the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform and the China National Knowledge Infrastructure. Meanwhile, the osteoarthritis disease targets were obtained through the genome annotation database platform (GeneCards) and the DrugBank database, and the target proteins obtained above were standardized using the Uniprot (https://www.uniprot.org ) database standardization of names. Then, the Venn diagram was created by taking the intersection of the active ingredient and the target of the disease, and the "active ingredient-target" network was constructed and analyzed using Cytoscape 3.7.2 software. At the same time, the intersecting targets were imported into the Search Tool for the Retrieval of Interaction Gene/Proteins database to build a protein-protein interaction network and to screen the core targets; the intersecting targets were visualized by using the Database for Annotation, Visualization and Integrated Discovery 6.8 database for gene ontology functional analysis and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, and construct the "active ingredient-target-pathway" network. Finally, the main active ingredients of the formula for tonifying the kidney and invigorating the blood were validated by molecular docking with the core targets. Results: A total of 194 active ingredients and 365 targets of the Bushen Huoxue formula were collected, 776 targets for osteoarthritis diseases and 96 targets for the intersection of active ingredients and diseases. The Kyoto Encyclopedia of Genes and Genomes enrichment analysis yielded 104 relevant pathways, including tumor necrosis factor signaling pathways, cancer signaling pathways, nucleotide-binding oligomerization domain-like receptor signaling pathways, Toll-like receptors signaling pathways, and osteoclast differentiation, apoptosis, T-cell receptor signaling pathway, and other related pathways. The molecular docking results showed good binding of the main active ingredients to the core targets. Conclusion: This study shows that the treatment of osteoarthritis involves multicomponent, multitarget, and multipathway processes. The mechanism of anti-inflammatory, antioxidant, inhibition of cartilage matrix degradation, and reduction of subchondral bone destruction may be an important mechanism for the therapeutic effect.